IMPACT WINDOWS LITHOLOGICAL PRODUCTIVITY WELLS - , Ю. М. (Municipal economy of cities. Series: «Economy science», 2013)
The analytical solution to take into account the impact on productivity lithological window wells. Based on theoretical research conclusions on account of the resistance box in the calculations unstable mode filtering.